If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -4) = -3x + 27 Reorder the terms: 2(-4 + x) = -3x + 27 (-4 * 2 + x * 2) = -3x + 27 (-8 + 2x) = -3x + 27 Reorder the terms: -8 + 2x = 27 + -3x Solving -8 + 2x = 27 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -8 + 2x + 3x = 27 + -3x + 3x Combine like terms: 2x + 3x = 5x -8 + 5x = 27 + -3x + 3x Combine like terms: -3x + 3x = 0 -8 + 5x = 27 + 0 -8 + 5x = 27 Add '8' to each side of the equation. -8 + 8 + 5x = 27 + 8 Combine like terms: -8 + 8 = 0 0 + 5x = 27 + 8 5x = 27 + 8 Combine like terms: 27 + 8 = 35 5x = 35 Divide each side by '5'. x = 7 Simplifying x = 7
| 7x+6=-20x^2 | | 5(7x-2)=10x | | 1/3(12x+18)=-2(3x-5)+96 | | 1/3(x-2)=4x-3(x-1)+17/3 | | 8(x-1)=5x+10 | | 1/7(x+3)=2x-5(4-x)-7 | | 3/4(5x+2)=4(3-2x)+13 | | (2x+7)=6x | | -144+4x^2=0 | | 4x^2-33x+45=-8x+9 | | (2m+4)+m=10 | | (2L+4)+L=10 | | 12-60x+75x^2=0 | | 5(x+3)+34=-2x | | 12-60x+5x^2=0 | | 6x+5y=34 | | 3s^2+5s-2=0 | | 5(x+6)=3(x+4) | | x+20+2x=-10-2x | | x^2+17x-51=9x-3 | | 2z/3-3/2=3z/2-17/3 | | x^2-11x+26=8 | | 36+48x+16x^2=0 | | -2(p-5)+7p=-6 | | -7f=72-f | | 2n+8=2-6 | | -15x+5x^2=0 | | 8(7x-3)=24x | | (10x+10−x)/(10x−10−x)=5 | | 13(x-2)=8x+4 | | 4x+8=15x-25 | | [3x]+8=9 |